Association between household income and gestational weight gain among pregnant women in Palembang - Faustina, Corinna; Melizah, Ardesy; Liberty, Iche Andriyani (Indonesian Nutrition Association, 2025)
Palembang is the city with the highest incidence of anemia in 2023, a condition that linked to maternal malnutrition. Gestational weight gain (GWG) is one of the indicator of maternal nutritional status. One of the factor that may influence the nutritional status is household income because it determines how a person afford their own nutrition. This study used a cross-sectional design and was conducted from August to October 2024. Data collection involved body weight measurement using the TANITA BC-601 and structured questionnaires. GWG was calculated as the difference between current body weight and pre-pregnancy weight, then the adequacy of GWG was assessed by comparing current weight with the ideal weight for gestational age. Eligible participants included singleton pregnant women without chronic illnesses who had completed the triple elimination program and received antenatal care at public health centers or private midwifery practices. Data analysis was performed with Chi Square analysis by using SPSS 27th version.